Combined effects of inspiratory and core muscle training on respiratory and core muscle function, limb muscle oxygenation and swimming performance - Pratama, A. B.; Chidnok, W.; Yimlamai, T. (Journal of Sports Sciences, 2026)
This study examined the effects of core training (CMT), inspiratory muscle training (IMT) and their combination (CIT) on strength and endurance of respiratory and core muscles, muscle oxygenation and swimming performance. Twenty-five competitive male swimmers, aged 15-20 years, were randomly assigned to one of three groups: CMT (n = 9), who performed core exercises; IMT (n = 8), who underwent inspiratory threshold-load training at 60-80% of maximal inspiratory pressure (MIP); or CIT (n = 8), who performed both, three times per week for 6 weeks in addition to their swimming training. MIP and inspiratory muscle endurance (IME), core strength and endurance, intercostals (IC) and vastus lateralis (VL) muscle oxygenation, and swimming performance were measured before and after intervention. Whilst CIT and IMT significantly improved MIP and IME, core strength and endurance were increased after CIT and CMT. Interestingly, only CIT showed a greater improvement in swim time (-4.74%, P < 0.001) compared to CMT and concomitantly increased VL, but not IC muscle deoxygenation post-swim. These findings suggest that supplementing 6 weeks of CIT to usual swimming training produced greater improvement in swimming performance compared to CMT, but not IMT, partly through improving oxygen extraction in locomotor muscles in young swimmers.